Prediction of fluid responsiveness following liver compression in pediatric patients with single ventricle physiology. Issue 5 (22nd February 2022) - Lee, Ji‐Hyun; Jang, Hwan‐Suk; Kang, Pyoyoon; Song, In Sun; Ji, Sang‐Hwan; Jang, Young‐Eun; Kim, Eun‐Hee; Kim, Hee‐Soo; Kim, Jin‐Tae
Abstract: Introduction: The role of liver compression in predicting fluid responsiveness in children with a single ventricle has never been evaluated. The purpose of this study was to assess whether blood pressure changes during liver compression predict fluid responsiveness in children with single ventricle physiology. Methods: This prospective, interventional study included children aged 3 months to 5 years who underwent surgery for bidirectional cavopulmonary shunt or extracardiac Fontan operation. Before fluid loading, the right upper abdomen was compressed at 30 mmHg for 10 s, and changes in the blood pressure waves were recorded before administering 10 ml kg −1 of crystalloid solution. Systolic arterial pressure, diastolic arterial pressure, central venous pressure, pleth variability index, respiratory variation in aortic blood flow peak velocity, and stroke volume were measured before and after fluid loading. A volume responder was defined as a patient with >15% increase in stroke volume index. Results: Thirty patients underwent bidirectional cavopulmonary shunt (15 responders and 15 non‐responders), and 32 underwent Fontan surgery (17 responders and 15 non‐responders). In children with bidirectional cavopulmonary shunt, Δsystolic arterial pressure > 8 mmHg (sensitivity 76.9% and specificity 93.3%), Δdiastolic arterial pressure > 7 mmHg (sensitivity 69.2% and specificity 93.3%), and Δmean arterial pressure > 7 mmHg (sensitivity 69.2% and specificity 100%) during liver compression predicted fluid responsiveness. The areas under the receiver operating characteristic curves of Δsystolic arterial pressure, Δdiastolic arterial pressure, and Δmean arterial pressure were 0.928, 0.859, and 0.874 (all p  < .001). In children who underwent Fontan surgery, only Δsystolic arterial pressure > 16 mmHg was predictive of fluid responsiveness (sensitivity of 41.2% and specificity of 100%), with the areas under the receiver operating characteristic curves curve of 0.786 ( p  < .001). Pleth variability index and respiratory variation in aortic blood flow peak velocity had no predictive value for fluid responsiveness after both types of surgeries. Discussion: In BCPS patients, liver compression increases the inferior vena cava flow which directly leads to an increase in preload. On the other hand, blood flow from the liver drains directly into the pulmonary arteries in Fontan circulation. Because of this characteristics for preload determination, the clinical application of liver compression to monitor hemodynamic changes might be more useful in patients with bidirectional cavopulmonary shunt than those with Fontan circulation. Conclusion: Increase in blood pressure induced by liver compression is predictive of fluid responsiveness in children with single ventricle physiology.